Depth‐Dependent Geometry of the Liquiñe‐Ofqui Fault Zone and Its Relation to Paths of Slab‐Derived Fluids. Issue 21 (11th November 2017) - Catalán, N.; Bataille, K.; Araya, R.
Abstract: Using a nonhomogeneous elastic model for the south Chile subduction zone, we calculate the depth‐dependent geometry of the Liquiñe‐Ofqui Fault Zone (LOFZ), considering that faults develop where shear stress is maximum. Shear stress develops due to the oblique subduction process, depending on shear modulus which varies as a function of the amount of fluids within the overriding plate. Regions with different values of shear modulus are obtained by the geometries of isotherms calculated from a thermal model. Based on the principle that fluids move from higher to lower pressure regions, we calculate paths of fluids from the subducting slab toward the free surface. In the vicinity of the volcanic arc, the obtained fluid paths agree with the geometry of the LOFZ, suggesting that margin‐parallel strike‐slip faults could serve as pathways for fluids through the overriding plate in oblique subduction zones. Key Points: We calculate the depth-dependent geometry of margin-parallel strike-slip faults, in relation to the Liquiñe‐Ofqui Fault Zone Modeling results suggest a relation between margin-parallel strike-slip faults and slab-derived fluids within oblique subduction zones